Mission for/as Reconciliatory Emancipation: Re‐visiting Bishop Masilamani Azariah's Theology of Mission - Samuel, Joshua (International review of mission, 2020)
Since Christian mission in the way of Jesus Christ is best understood and experienced in the fringes of the society, it is imperative that we listen to and learn from marginalized voices. Keeping this in mind, this article looks at the relevance of the theology of mission of the Dalit theologian and activist Masilamani Azariah, who served as a Bishop of the Church of South India in the 1990s. It seeks to highlight his pioneering work, which was discomforting for some dominant caste Indian Christians, in challenging the Indian church as well as the global ecumenical movement to speak up and act against untouchability and caste discrimination. Using Azariah's radical perspectives of mission as a lens, and employing the framework of reconciliatory emancipation, a theological concept explicated by the American political theologian Mark Taylor, this essay proposes that the mission of the church that endeavours to be holistic and Christ-centred would and should be committed to the empowerment and healing of the oppressed, driven by a burning prophetic rage against injustice, even while retaining the space for forgiveness and repentance, with the ultimate goal of building the kingdom of God that transcends divisive and discriminating boundaries.